Microtubule organization by the budding yeast spindle pole body - Knop, Michael; Pereira, Gislene; Schiebel, Elmar (Biology of the cell, 1999)
In budding yeast microtubule organizing functions are provided by the spindle pole body (SPB), a multi-layered structure that is embedded in the nuclear envelope throughout the cell cycle. The SPB organizes the nuclear and cytoplasmic microtubules which are spatially and functionally distinct. Microtubule formation in yeast requires the Tub4p-complex, containing the γ-tubulin Tub4p, and two additional proteins, the SPB components Spc97p and Spc98p. The Tub4p complex assembles in the cytoplasm and is then anchored to the sides of the SPB which organize microtubules. This is achieved by the binding of Spc97p and Spc98p to so-called γ-tubulin complex binding proteins (GTBPs) at the SPB. Spc72p is the yeast GTBP at the cytoplasmic side of the SPB, while Spc110p is the nuclear GTBP. Both GTBPs control the number of Tub4p complexes associated with the SPB and thereby the number of microtubules formed. In addition, the GTBPs may regulate the activity of the Tub4p complex. Homologues of Spc97p and Spc98p have been identified from yeast to mammalian cells and these are also part of γ-tubulin complexes, suggesting that these related proteins may also interact with GTBPs at the centrosome. Candidates for GTBPs have been identified in mammalian and insect cells.